2004
DOI: 10.1007/s11046-004-2844-y
|View full text |Cite
|
Sign up to set email alerts
|

A case of eumycetoma due to Madurella grisea in northern Brazil

Abstract: A case of mycetoma caused by the black fungus Madurella grisea in northern Brazil is reported. The lesion was located on the patient's right foot without bone involvement. Clinical samples were collected by opening the fistules with a scalp and the grains removed for microbiological and histopathological analyses. Although mycetoma caused by M. grisea has been previously reported in Brazil, this is the first time that of this fungus has been identify in this particular region of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In view of the wide polymorphism which Madurella species often showed, species differentiation of Madurella can be complemented by differences in sugar assimilation and optimal growth temperature (4,14). M. mycetomatis grows well at 37°C and assimilates lactose but not sucrose, whereas M. grisea stops growth at 37°C and assimilates sucrose but not lactose (4,25). Our results indicated that strain TMMU3956 could tolerate 42°C but assimilates neither sucrose nor lactose.…”
Section: Vol 48 2010mentioning
confidence: 67%
See 1 more Smart Citation
“…In view of the wide polymorphism which Madurella species often showed, species differentiation of Madurella can be complemented by differences in sugar assimilation and optimal growth temperature (4,14). M. mycetomatis grows well at 37°C and assimilates lactose but not sucrose, whereas M. grisea stops growth at 37°C and assimilates sucrose but not lactose (4,25). Our results indicated that strain TMMU3956 could tolerate 42°C but assimilates neither sucrose nor lactose.…”
Section: Vol 48 2010mentioning
confidence: 67%
“…Morphologically, strain TMMU3956 is more similar to M. mycetomatis than M. grisea (4,25), but in most cases, TMMU3956 formed granularis rather than woolly colonies and grew most slowly. In view of the wide polymorphism which Madurella species often showed, species differentiation of Madurella can be complemented by differences in sugar assimilation and optimal growth temperature (4,14).…”
Section: Vol 48 2010mentioning
confidence: 95%
“…Reported cases of mycetoma caused by T. grisea originated from South America and India. Unconfirmed reports were published from North and Central America, Africa, and Asia ( Green & Adams 1964 , Butz & Ajello 1970 , Mahgoub 1973 , Venugopal et al 1990 , Vilela et al 2004 ). In most of these publications, identification was based on morphological or physiological properties and may have been misidentifications ( Desnos-Ollivier et al 2006 ).…”
Section: Discussionmentioning
confidence: 94%
“…From 1980 to 2014, the main bacterial agents identified in Brazil were Nocardia brasiliensis [15,26,27–32], Nocardia asteroides [15,33], Nocardia caviae [34], Actinomadura madurae [13,35,36], Actinomadura pelletieri [14], and Streptomyces somaliensis [15]. For eumycetoma were Madurella mycetomatis [15,25,37,38], Madurella grisea [39–45], Acremonium falciforme [46], Acremonium kiliense [47], Scedosporium apiospermum [12,18,48,49,50], Fusarium solani [51], Exophiala jeanselmei [44,52,53] and Aspergillus sp. [12].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%